ANÃLISIS DE UN CURSO DE E-LEARNING PARA LA RECUPERACIÃ“N DEL MÃ“DULO PENDIENTE DE PROGRAMACIÃ“N EN LOS CICLOS FORMATIVOS DE GRADO SUPERIOR DE LA FAMILIA PROFESIONAL DE INFORMÃTICAY COMUNICACIONES - Nanclares, JesÃºs DiÃ©guez (European Scientific Journal, ESJ, 2015)
The vocational training superior degrees of the family â€œComputer Science and Communicationsâ€ contain high complexity professional modules, specially those related to Programming. Thus, there are a big number of students that fail to get the degree in the two years that these courses take. This research tries to verify if by performing an e-learning course aimed to those students that have previously failed the programming module, can help them to improve results in September exams. For this research, a whole course has been created, including contents specified in the curriculum of the â€œProgrammingâ€ module of the vocational training superior degrees â€œWeb Applications Developmentâ€ and â€œCross-platform Applications Developmentâ€. The course was conducted during the summer and several schools of Castilla-La Mancha participated in it. The results obtained showed that the use of this type of courses help improving results in September exams. Offering this sort of courses can prevent students that have previously failed from spending a whole year with a resit module and can help students that passed to improve their skills to deal with more success the modules of the second year.